TINGKAT MOTIVASI DAN HASIL BELAJAR LARI CEPAT SISWA MI AL- IKHLAS BABADAN - Kosim; Seni Oktriani; Fauzan Effendy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of students’ learning motivation and learning outcomes in the 60-meter sprint among fifth-grade students of MI Al-Ikhlas Babadan. The research method used was a quantitative descriptive method with data collection techniques through learning motivation questionnaires and a 60-meter sprint performance test. The subjects of the study consisted of fifth-grade students participating in Physical Education, Sports, and Health (PJOK) learning activities. The results of the study showed that the students’ learning motivation was categorized as high. This could be seen from the students’ enthusiasm, spirit, and active participation in learning the 60-meter sprint. In addition, the students’ learning outcomes in the 60-meter sprint material obtained a mastery score of 12% in the very good category and 54% in the good category, and had achieved the Minimum Mastery Criteria (KKM) set at 73. High learning motivation had a positive influence on students’ learning outcomes in the 60-meter sprint learning process. Based on the results of the study, it can be concluded that high students’ learning motivation can support the improvement of learning outcomes in the 60-meter sprint. Therefore, teachers are expected to create interesting and enjoyable learning activities in order to improve students’ motivation and learning outcomes.